Determination of Three Alkyl Camphorsulfonates as Potential Genotoxic Impurities Using GC-FID and GC-MS by Analytical QbD - Kyoungmin Lee; Wokchul Yoo; Jin Hyun Jeong (Separations, 2022)
Camphorsulfonic acid salts are commonly used in the manufacturing production of active pharmaceutical ingredients (APIs) and have the potential to form alkyl camphorsulfonates, which can be considered as potential genotoxic impurities (PGIs). Alkyl camphorsulfonates should be controlled using the Threshold of Toxicological Concern (TTC) when detected in APIs due to their genotoxicity. An in silico study utilizing the ICH M7 guideline was performed in order to classify the alkyl camphorsulfonates that can be produced from the reaction of camphorsulfonic acid salts with methanol, ethanol, and isopropyl alcohol, which are commonly used solvents in API manufacturing processes. Two sensitive, reproducible, and accurate analytical methods using GC-FID and GC-MS were developed using the analytical Quality By Design (QbD) approaches for the quantitation of three alkyl camphorsulfonates in APIs satisfying the control limit of PGIs according to the TTC. The detection limits of the GC-FID method were found to be between 1.5 to 1.9 ppm, and the detection limits of the GC-MS method were found to be between 0.055 to 0.102 ppm. The method was validated in terms of accuracy, linearity, precision, detection limit, quantitation limit, specificity and robustness.